2015
DOI: 10.3892/ol.2015.3759
|View full text |Cite
|
Sign up to set email alerts
|

Function and clinical potential of microRNAs in hepatocellular carcinoma

Abstract: Abstract. MicroRNAs (miRNAs) are small non-coding RNAs involved in the initiation and progression of several types of human cancer, including hepatocellular carcinoma (HCC), which is one of the most common types of cancer and the third leading cause of cancer-related mortality worldwide. Mounting evidence has demonstrated that miRNAs play a vital role in HCC, hepatitis, alcoholic liver disease, liver cell development and the metabolic functions of the liver. The aim of the present review was to summarize the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 157 publications
0
16
0
1
Order By: Relevance
“…Identifying the biomarker proteins and their regulating miRNAs that are essential for HCC progression may provide promising therapeutic opportunities. Many miRNAs have been found to be dysregulated in HCC and function as oncogenes or tumor suppressors, depending on their targets in HCC tumorigenesis . Recently, studies have found that miR‐24 acts as an oncogene in several tumors, including HCC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying the biomarker proteins and their regulating miRNAs that are essential for HCC progression may provide promising therapeutic opportunities. Many miRNAs have been found to be dysregulated in HCC and function as oncogenes or tumor suppressors, depending on their targets in HCC tumorigenesis . Recently, studies have found that miR‐24 acts as an oncogene in several tumors, including HCC .…”
Section: Discussionmentioning
confidence: 99%
“…Many miRNAs have been found to be dysregulated in HCC and function as oncogenes or tumor suppressors, depending on their targets in HCC tumorigenesis. 3,[9][10][11][12] Recently, studies have found that miR- It is generally accepted that miRNAs exert their function through regulating the expression of their downstream target genes. In this study, we identified MT1M as a target of miR-24-3p in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-34a showed tumor suppressor effects by reducing cell migration and invasion via targeting the hepatocyte growth factor (HGF) receptor c-MET. In contrast, miR-21 represented an oncogenic miRNA in HCC that induce cell growth, invasion, and metastasis by inhibiting PTEN gene activity (13).…”
Section: Editorialmentioning
confidence: 99%
“…The increased de novo FAS in cancer cells occurs through multiple mechanisms, most of which involve the abnormal expression of key lipogenic enzymes and miRNAs. miRNAs play an important role in HBV‐induced lipid metabolism disorders and HBV‐related liver diseases .…”
Section: Introductionmentioning
confidence: 99%